EFFECTS OF SILICON NUTRIENT ON MELON (Cucumis melo cv. Melon Manis Terengganu) GROWTH AND POWDERY MILDEW (Podosphaera xanthii) INCIDENCE - Chong Sok Leng
Plant diseases, including powdery mildew are common biotic stresses affecting melon cultivation. Several studies have reported that silicon (Si) is effective in controlling plant diseases. However, there is still a lack of silicon studies highlighting the effectiveness of silicic acid (liquid form of silicon) on plant growth and disease control. Cucurbits are Si intermediate-accumulator, where highly soluble Si (e.g. silicic acid) is needed for efficient transport into the plant system. Therefore, the Si nutrient has a potential to improve melon plant growth and development, while also reducing the most common fungal diseases of melons such as powdery mildew. There were three objectives in this study; firstly to determine the effects of Si nutrient towards melon growth; secondly to determine the potential of Si nutrient in delaying powdery mildew disease on melon and; thirdly to understand the impact of Si application on the uptake and accumulation of other nutrient elements in melon (leaves and roots). A randomized complete block design (RCBD) was adopted for the experimental plot design that were conducted in selected greenhouses by using melon cv. melon manis Terengganu (MMT) as tested plant samples. Different Si treatments of: 0.1% Si (v/v); 0.5% Si (v/v); 1.0% Si (v/v); and 1.5% Si (v/v) were applied weekly through soil drenching and foliar spraying. Throughout this study, melon plant growth and development, powdery mildew disease (at field, in vitro and in planta experiments), fruit quality and nutrient uptake were analysed. T